Evaluation of bioremediation strategies for treating recalcitrant halo-organic pollutants in soil environments - Sadañoski, Marcela Alejandra (2020)
The aim of this study was to investigate the bioremediation potential of polychlorinated biphenyls (PCBs) in soil, mimicking three strategies: (a) mycoaugmentation: by the addition of Trametes sanguinea and Pleurotus sajor-caju co-cultures immobilized on sugarcane bagasse; (b) biostimulation: by supplementation of sugarcane bagasse; and (c) natural attenuation: no amendments. The experiments were done in microcosms using Ultisol soil. Remediation effectiveness was assessed based on pollutants content, soil characteristics, and ecotoxicological tests. Biostimulation and mycoaugmentation demonstrated the highest PCBs-removal (approx. 90%) with a significant toxicity reduction at 90 d. The studied strains were able to survive during the incubation period in non-sterilized soil. Laccase, manganese-peroxidase and endoxylanase activities increased significantly in co-cultures after 60 d. Sugarcane bagasse demonstrated to be not only a suitable support for fungal immobilization but also an efficient substrate for fungal colonization of PCBs-contaminated soils. Mycoaugmentation and biostimulation with sugarcane bagasse improved oxidable organic matter and phosphorous contents as well as dehydrogenase activity in soil. Therefore, biostimulation with sugarcane bagasse and mycoaugmentation applying dual white-rot fungal cultures constitute two efficient bioremediation alternatives to restore PCBs-contaminated soils.